Naked came the Florida man - Dorsey, Tim (Dorsey, Tim. Serge Storms series., 2020)
Though another devastating hurricane is raking Florida, its awesome power can<U+2019>t stop the Sunshine State<U+2019>s most loyal son, Serge A. Storms, from his latest scenic road trip: a cemetery tour. With his best bro Colman riding shotgun, Serge hits the highway in his <U+2019>69 gold Plymouth Satellite, putting pedal to the metal on a grand tour of the past. Beginning in Key West, the sunshine boys<U+2019> odyssey includes a forgotten mass grave in Palm Beach county holding the remains of African Americans killed by the Great Hurricane of 1928, and the resting place of one world-famous television dolphin (RIP Flipper) from the 1960s. But one deadland<U+2014>a haunted old sugar field<U+2014>holds more than just the bones of those who<U+2019>ve passed. For years, local children have whispered about a boogeyman hiding among the stalks. Could it be the same maniac known as Naked Florida man who<U+2019>s been raising hell all over the place? There are few things Serge loves more than solving a good mystery and bestowing justice on miscreants who sully his beloved home<U+2019>s good name. With his partner bong boy, Florida<U+2019>s psycho superhero will find the truth in this hilariously violent delight<U+2014>packed with history, lore, and plenty of motel antics<U+2014>from the insanely ingenious Tim Dorsey.